A 2007 Social Accounting Matrix (SAM) for Zambia - Chikuba, Zai; Syacumpi, Malunga; Thurlow, James (Zambia Institute for Policy Analysis and Research, 2013)
This paper documents a Zambian Social Accounting Matrix (SAM) for the year 2007. The national SAM is built using a new input-output use tables, national accounts, government budgets, and balance of payments, and so provides a detailed representation of the Zambian economy. It separates 44 activities and commodities; labor is disaggregated by education level; and households by rural and urban per capita expenditure quintiles. Information on labor is drawn from the 2006 Living Conditions Monitoring Survey. Finally, the SAM identifies government, investment and foreign accounts. It is therefore an ideal database for conducting economywide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.